Climate Change: Uncertainty for Hydropower Development in Nepal - Pathak, Mahesh (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
There is a worldwide consensus that climate change is a real, rapidly advancing and widespread threat facing this century. This is a crucial issue in Himalayan and special in Nepal because of its possible impact on water resource, biodiversity, and consequence on economic growth of the region. The increase trend of glacial retreat and variability on temperature and participation has the direct impact on the water resource and hydropower development. Mountain regions are particularly vulnerable, both because warming trends are higher and the impacts are magnifed by the extreme changes in altitude over small distances. It indicates the great variability of hydro-climatic variability in major rivers and their tributaries. Decrease runoff will have direct impact on the hydropower development, but there is uncertainty about the role of spatial variability of changing climatic scenarios and their possible impact for hydropower development in large and middle rivers. This paper presents the scenarios of climate change in Nepal in terms of hydro-climatic variability. The frst part describes hydro-climatic variability and its uncertainty for hydropower development, and the second part deals with the mitigation of uncertainties. Key words: Climate change; Deglaciation; GLOF; Water resource; Hydrological cycle; Hydropower; Himalayas; Nepal DOI: 10.3126/hn.v6i0.4190 Hydro Nepal Vol 6, January 2010 Page : 31-34 Uploaded Date: 24 January, 2011